2020
DOI: 10.1080/00365521.2020.1790647
|View full text |Cite
|
Sign up to set email alerts
|

Experiences of using vedolizumab in the treatment of inflammatory bowel disease in the East Midlands UK – a retrospective observational study

Abstract: Purpose: Clinical trials have demonstrated efficacy of vedolizumab in ulcerative colitis (UC) and Crohn's disease (CD). Further real-world data is needed to inform clinical practice. The primary outcome was to assess corticosteroid-free and clinical remission after vedolizumab initiation. Secondary outcomes included effect on disease activity scores, biochemical markers, concomitant drug use, endoscopic remission, surgical intervention, hospital admissions and adverse events. Materials and methods: A multi-cen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 46 publications
1
4
0
Order By: Relevance
“…Our analysis showed that 90.3% of all patients who reached week 54 were without corticosteroids. This result was consistent with the reports by Kopylov et al (86.2% at week 52), 25 Stallmach et al (83% at week 54), 33 and White et al (85% at week 52), 46 which similarly observed a significant decrease in concomitant corticosteroid use compared with baseline. Steroid-free clinical remission at week 54 was the primary endpoint in the study conducted by Amiot et al (40.5% of all patients) 39 and a secondary endpoint of the pivotal GEMINI-1 trial (41.8% of patients who continued to receive vedolizumab every 8 weeks and 44.8% of patients who continued to receive vedolizumab every 4 weeks), 10 which is similar to our study (47% of all patients).…”
Section: Discussionsupporting
confidence: 92%
“…Our analysis showed that 90.3% of all patients who reached week 54 were without corticosteroids. This result was consistent with the reports by Kopylov et al (86.2% at week 52), 25 Stallmach et al (83% at week 54), 33 and White et al (85% at week 52), 46 which similarly observed a significant decrease in concomitant corticosteroid use compared with baseline. Steroid-free clinical remission at week 54 was the primary endpoint in the study conducted by Amiot et al (40.5% of all patients) 39 and a secondary endpoint of the pivotal GEMINI-1 trial (41.8% of patients who continued to receive vedolizumab every 8 weeks and 44.8% of patients who continued to receive vedolizumab every 4 weeks), 10 which is similar to our study (47% of all patients).…”
Section: Discussionsupporting
confidence: 92%
“…Like the RBS and SFS, the PMS is often used in clinical trials and observational studies in patients with UC 18,19 . Data reported here show that PMS is improved as early as month 1 in both the retreatment and dose escalation subpopulations and therefore may be another suitable endpoint for non‐invasive assessment of response following treatment interruption in patients with UC treated with tofacitinib 10 mg BID.…”
Section: Discussionmentioning
confidence: 88%
“…It would appear that this increase in vedolizumab prescription is in keeping with national trends. A retrospective cohort study conducted in the East Midlands showed that 45% of patients were prescribed vedolizumab as first‐line therapy [22] and 79% in another UK multicentre cohort of patients over 60 [23].…”
Section: Discussionmentioning
confidence: 99%